2012
DOI: 10.4236/abb.2012.326087
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis in amphibian development

Abstract: Amphibians and more particularly X. laevis are models often used for studying apoptosis during embryonic development. Using several methods, searchers determined the localization of programmed cell deaths (PCD). Several experimental methods also have been used to understand the regulatory mechanisms of apoptosis, throughout development, contributing to elucidate the general action of several genes and proteins. Apoptosis occurs very early, with a first program under control of maternal genes expressed before M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 81 publications
2
17
0
Order By: Relevance
“…A first one was observed at the onset of gastrulation, and depended on the maternal genes expressed at mid blastula transition (MBT). This first wave seemed to be related to the elimination of abnormal cells [42]. At gastrulation, a second wave of apoptotic cells was visualised in Xenopus laevis [39].…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…A first one was observed at the onset of gastrulation, and depended on the maternal genes expressed at mid blastula transition (MBT). This first wave seemed to be related to the elimination of abnormal cells [42]. At gastrulation, a second wave of apoptotic cells was visualised in Xenopus laevis [39].…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies showed that physiological PCD was observable at the onset of gastrulation (stage 10.5) in Xenopus laevis development [39,42,43].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Only a few studies regarding the calpains have been realized in amphibian [18]. The aim of the present paper is to compare during the embryogenesis of Xenopus laevis the expression profiles of a well-known calpain, the CAPN1, with a calpain that is less studied, the CAPN-8b.…”
Section: Introductionmentioning
confidence: 99%